Evaluasi dan Analisis Kekuatan Jembatan Pipa Armco Berdasarkan Tegangan Izin pada Proyek Pembangunan Jalan Inspeksi JDU-JDP Ibu Kota Negara (IKN) - Hariyanto, Hariyanto; Fathurrahman, Fathurrahman; Febrianty, Ruliana (SENTRI: Jurnal Riset Ilmiah, 2026)
The Armco pipe bridge is a Corrugated Steel Pipe (CSP) structure that relies on soil-structure interaction to support road infrastructure loads. This study evaluates the structural strength of the Armco pipe bridge on the JDU-JDP Inspection Road construction project in the National Capital City (IKN) using the Allowable Stress Design (ASD) method and the Ring Compression Theory referring to ASTM A796 and SNI 1725:2016. Data processing combined manual calculation in Excel with numerical simulation using ETABS software. The pipe under study has a diameter of 2,100 mm, a plate thickness of 3.5 mm, and a soil cover depth of 2.1 m. The results show an actual stress (σactual) of 194.310 MPa, below the allowable stress (σallowable) of 210 MPa with a safety factor of 2, giving a stress ratio of 0.925 and confirming that the structure is safe. The shear stress reaches 88.340 MPa, also within the allowable limit. Deflection analysis records a deflection of 2.699 mm, far below the maximum allowable deflection of 105 mm. The soil cover depth is shown to influence load distribution: a deeper embankment widens the spread of live load before it reaches the pipe crown, reducing the vertical pressure received by the pipe wall. These findings confirm that the Armco pipe bridge is a safe and efficient structural solution.